2001
DOI: 10.1016/s0167-4889(01)00092-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific secretion of gel-forming mucins and TFF peptides in HT-29 cells of mucin-secreting phenotype

Abstract: Trefoil factor family (TFF) peptides are typical secretory products of mucin-producing cells, e.g. of the gastrointestinal tract. Here, the expression and secretion of mucins and TFF peptides was studied in the HT-29 cell line throughout cellular growth and differentiation in relation to a mucin-secreting (HT-29 MTX) or an enterocyte-like (HT-29 G(-)) phenotype. mRNAs of several MUC and TFF genes were expressed in both cell subpopulations. However, for most MUC and TFF genes, the expression appeared strongly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
0
39
0
1
Order By: Relevance
“…7C and Table 1) of inhibin␣ and TFF1 in all cell lines in which these genes are basally silent. When examined at the protein level, the GATA-5 overexpression resulted in expression of the secreted TFF1 protein (15) in the media of the cell cultures (Fig. 7D).…”
Section: Resultsmentioning
confidence: 99%
“…7C and Table 1) of inhibin␣ and TFF1 in all cell lines in which these genes are basally silent. When examined at the protein level, the GATA-5 overexpression resulted in expression of the secreted TFF1 protein (15) in the media of the cell cultures (Fig. 7D).…”
Section: Resultsmentioning
confidence: 99%
“…This difference between TFF2 RNA and protein expression has been previously reported and could potentially be explained by impaired accessibility of the epitope or a defect of translation. 30 Galectin 3 is a member of the ␤-galactosidase-binding lectin family. 31 It is involved in diverse physiological and pathological processes, including the regulation of cell growth, cell differentiation and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation was induced by NaB, which is a well-known differentiation inducer of colonic epithelial cells (Kim et al, 1980). It has been demonstrated that NaB induces differentiation of colon-derived cell lines into mucus-secreting goblet cells that produce mucin glycoproteins and into absorptive enterocytes, which are characterised by elevated ALP activity (Wice et al, 1985;Schroy et al, 1994;Velcich et al, 1995;Gouyer et al, 2001). Induction of differentiation was followed by measurement of ALP activity in cell lysates (Colony and Neutra, 1983) and by RT -PCR detection of mRNA levels of two differentiation markers, CEA (Huitric et al, 1976;Velcich et al, 1995) and mucin 3 (MUC3) (Velcich et al, 1995;Gouyer et al, 2001;Gaudier et al, 2004).…”
Section: Expression Of D-type Cyclins During Induction Of Differentiamentioning
confidence: 99%